Community Preparedness for Health Disasters: A Study of Community Health Literacy - Lamsir, Seno (Oshada, 2025)
Background: Recent health disasters indicate that community preparedness is influenced not only by the availability of health services but also by community health literacy, which enables individuals to understand risks, assess health information, and make preventive decisions during emergencies. Method: This study employed a qualitative literature review approach to analyze the relationship between health literacy and community preparedness for health disasters. Results: The findings show that health literacy acts as a strategic determinant shaping risk perception, preventive behavior, psychosocial readiness, and community adaptive capacity during health crises. Community-based interventions, the involvement of community health workers, and cross-sector collaboration were identified as effective mechanisms for strengthening health literacy and collective preparedness. Conclusion: Integrating community health literacy into disaster management policies and sustainable public health development programs is essential to enhance community preparedness and resilience in the face of health disasters.